A cross-sectional survey: Exploring future healthcare workers' intention to use cannabis through extended theory of planned behavior - Ho, Sze Wing Cherelle; WONG, Yuen Lung; Chung, Pui Hong (Frontiers in Public Health, 2022)
Cannabis is the most extensively abused drug, leading to multiple health burdens such as traffic accidents and psychosis. There is a global wave of legalisation of recreational and medical cannabis. This study aimed to understand future healthcare workers’ intention to use cannabis through extended Theory of Planned Behaviour (TPB). An online cross-sectional survey on cannabis, including validated survey tools and questions on demographics, knowledge, and constructs of the TPB was designed, and distributed during virtual classes in late 2020. Responses were obtained from the Faculty of Medicine of a local university. 996 responses were collected, of which 629 were complete and analysed. Age was the only demographic variable associated with cannabis use intention (p = 0.029). Respondents with intention had better knowledge of cannabis. All TPB and additional constructs, including perceived behavioural control (COR = 3.44, 95% CI 2.72-4.35, p < 0.001), descriptive norm (COR = 2.24, 95% CI 1.81-2.77, p < 0.001), injunctive norm (COR = 0.51, 95% CI 0.42-0.61, p < 0.001), attitude (COR = 1.23, 95% CI 1.18-1.28, p < 0.001), knowledge (COR = 1.08, 95% CI 1.03-1.14), and perceived availability (COR = 2.75, 95% CI 2.22-3.40, p < 0.001) were individually associated with intention. In the final multiple logistic regression model adjusted for age, only attitude (AOR = 1.19, 95% CI 1.13-1.25, p < 0.001) and perceived availability (p = 0.004) showed statistically significant associations with intention. Descriptive norm (standardised coefficient = 0.570) had better explanatory power than the injunctive norm (standardised coefficient = -0.143) in the model. Perceived behavioural control was associated with intention among respondents with negative to neutral attitudes towards cannabis (AOR = 2.48, 95% CI 1.63-3.77, p < 0.001), but not among those with positive attitudes. All TPB constructs positively correlated with the intention to use cannabis. Changing the attitudes and perceived control on cannabis use may be useful in preventing cannabis use.